ANALISIS VOLATILITAS DAN PERAMALAN KURS JUAL RUPIAH TERHADAP RIYAL ARAB SAUDI MENGGUNAKAN MODEL ARCH/GARCH - ROSSY NOVIYANA; ADAWIYAH ASTI KHALIL (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Exchange rate volatility is a phenomenon that affects economic stability, particularly in the context of international trade between Indonesia and Saudi Arabia. This research aims to analyze the volatility of the Rupiah selling rate against the Saudi Riyal and to forecast the exchange rate using the ARCH/GARCH modeling approach. This research employs daily secondary data obtained from the official website of Bank Indonesia for the period from May 2023 to July 2025. The analysis includes stationarity testing, differencing transformation, ARIMA modeling, heteroskedasticity testing, and the application of the ARCH/GARCH model. The best ARIMA model, based on the Akaike Information Criterion (AIC), is AR(2) AR(7) I(1) MA(2) MA(7). The Lagrange Multiplier (LM) test indicates the presence of heteroskedasticity, necessitating the use of the ARCH/GARCH model. Among several alternatives, the GARCH(2,1) model is selected as the best model due to its highest log-likelihood value, lowest AIC, and successful second LM test confirming the absence of residual heteroskedasticity. The GARCH(2,1) model demonstrates strong forecasting performance with an RMSE of 15.51, MAE of 11.38, Theil’s U2 of 0.98, and a covariance proportion of 0.994. Overall, this model is suitable as a forecasting tool for the Rupiah selling rate against the Riyal in the future.